Family Transformation as a Source of Early Childhood Character Education (Bandura's Social Cognitive Theory Perspective) - Sakti, Syahria Anggita (THUFULA, 2023)
The purpose of this research is to describe the shift of the family in its function as the main pillar in instilling character values in early childhood. The method used in this research is a focused interview method with a qualitative approach. The stages of instilling children's character in the family today are (1) knowledge (knowing), where children are given an understanding of the values, norms, and principles expected in the family. (2) acting, where children need to practice these values in real actions, and (3) habit, where the expected positive characters have been internalized in children so that they automatically and unconsciously act in accordance with these values. Later, this development can be integrated and directed in every school activity. Thus, character education can be well integrated into the school curriculum and extracurricular activities. Through this approach, it is hoped that the goal of character development in children can be achieved more effectively and sustainably.